Development and Implementation of Digital Teaching Materials for Fable Texts in Junior High Schools - Laely Syaudah; Yusida Gloriani; Dede Endang Mascita (PT Inovasi Pratama Internasional, 2024)
This study aims to elucidate the design, feasibility, and implementation of digital teaching materials for fable texts intended for junior high school (SMP/MTs) students, utilizing the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data were collected through classroom observations and questionnaires during fable text lessons. The questionnaires revealed that students disliked assignments related to fable text learning. In response, the author developed digital teaching materials for fable texts accessible via YouTube and live worksheet applications. Validation by subject matter and media experts indicated high feasibility, with scores of 91.43% and 90%, respectively. Implementation with students resulted in a comprehension rate of 90%, demonstrating that these digital teaching materials enhance student engagement and facilitate completion of fable text assignments. Consequently, these materials are recommended as supplementary resources for learning fable texts.